If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(z + 3) + -20 = 0 Reorder the terms: 6(3 + z) + -20 = 0 (3 * 6 + z * 6) + -20 = 0 (18 + 6z) + -20 = 0 Reorder the terms: 18 + -20 + 6z = 0 Combine like terms: 18 + -20 = -2 -2 + 6z = 0 Solving -2 + 6z = 0 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 6z = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 6z = 0 + 2 6z = 0 + 2 Combine like terms: 0 + 2 = 2 6z = 2 Divide each side by '6'. z = 0.3333333333 Simplifying z = 0.3333333333
| x*(x+6)=y | | 12x-5=-4 | | -4x+-6=-14 | | 2/4x-1=6 | | 20=10y-6y | | 2x+5y=10graph | | 3(x-1)-1=3x+2 | | 2X-11=X+6 | | 7-6x=16+3 | | 20W-34=17W-19 | | ln(3x-2)=3.5 | | 8x+18=y | | 16t^2-2t+885=390 | | 5x+20x=28x | | 4500=6x+540 | | 42y=24 | | 16t^3-2t+885=390 | | 0x+-2=1 | | s^2=3+s(7-4s) | | 2c+2+6c+-4= | | 2X-11=8+6 | | F(x)=6x^2-7 | | 2b-6+4=3b+8 | | 2X+1=4X-37 | | 5x+20y=350 | | 8W-9=7W+4 | | 16x+12=14x+18 | | 2l-3=l+4 | | 3x^2+x-27=0 | | 8W-9=7W-4 | | 8h-17=64 | | 2(x-1)+1=3 |